2009
DOI: 10.1016/j.jpedsurg.2008.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic decortication vs tube thoracostomy with fibrinolysis for empyema in children: a prospective, randomized trial

Abstract: Purpose Management of empyema has been debated in the literature for decades. Although both primary video-assisted thoracoscopic surgery (VATS) and tube thoracostomy with pleural instillation of fibrinolytics have been shown to result in early resolution when compared to tube thoracostomy alone, there is a lack of comparative data between these modes of management. Therefore, we conducted a prospective, randomized trial comparing VATS to fibrinolytic therapy in children with empyema. Methods After Institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
197
2
18

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(221 citation statements)
references
References 25 publications
4
197
2
18
Order By: Relevance
“…29 A study in the United States yielded similar estimates. 30 Thus, the 35% increase in empyema admissions observed in Australia following the introduction of the PCV7 has brought an additional expenditure of US$ 126 160-194 220 per year to the Australian health-care system. On the other hand, the reduction in pneumonia admissions has saved the health system US$ 3.8 million-6.1 million annually (based on United Kingdom cost-analysis data for pneumonia admissions).…”
Section: Discussionmentioning
confidence: 99%
“…29 A study in the United States yielded similar estimates. 30 Thus, the 35% increase in empyema admissions observed in Australia following the introduction of the PCV7 has brought an additional expenditure of US$ 126 160-194 220 per year to the Australian health-care system. On the other hand, the reduction in pneumonia admissions has saved the health system US$ 3.8 million-6.1 million annually (based on United Kingdom cost-analysis data for pneumonia admissions).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Sendo esta revisão de carácter retrospetivo com um número reduzido de doentes, e sem grupo de controlo, os resultados podem apenas comparar-se com outras séries.…”
Section: Discussionunclassified
“…9 À data da redação deste artigo, existem três estudos randomizados publicados que comparam a instilação intrapleural de fibrinolítico com a toracoscopia videoassistida (VATS), no tratamento de DPP complicados, na população pediátrica. [10][11][12] Os três concluem não haver diferenças estatisticamente significativas entre as opções terapêuticas no que diz respeito a duração de internamento, tempo de drenagem e taxa de falência terapêutica. [10][11][12] Este estudo foi realizado para avaliar e descrever os resultados da aplicação de um protocolo de utilização de fibrinolítico no tratamento de DPP complicado, nos doentes seguidos no nosso hospital.…”
unclassified
“…Two studies comparing fibrinolysis with VATS reported a fibrinolysis failure rate of 17% each. [19,20] Other prospective studies comparing fibrinolysis with normal saline or various doses of urokinase report fibrinolysis failure rates of 7 -24%. [7,8,21] A meta-analysis published in 2005 calculated the average failure rate of 64 empyema cases treated with primary fibrinolysis to be 9.3%.…”
Section: Discussionmentioning
confidence: 99%